Pyroptosis-Related Subtypes Predict the Response of Clear Cell Renal Cell Carcinoma to Targeted Therapy - Jinpeng Ma; Zhijian Kang; Guang Yang; Xinyue Wang; Minggui Si; Yuting Wang; Guangbin Li; Shiyu Bai; Fanshu Zeng; Min Li; Ziqi Wang; Lu Wang; et al. (Frontiers in Bioscience-Landmark, 2023)
Background: Pyroptosis plays a crucial role in anti-tumor immunity and in formation of the immune microenvironment. However, whether pyroptosis is involved in the progression of clear cell renal cell carcinoma (ccRCC) is still unclear. Personalized treatment of ccRCC requires detailed molecular classification to inform a specific therapy. Methods: Molecular subtyping of ccRCC was performed based on consensus clustering of pyroptosis-related genes. The characteristics of these molecular subtypes were explored at the genome, transcriptome and protein levels. Single-cell RNA sequencing and CIBERSORT analysis were used to analyse the immune microenvironment of ccRCC, while Lasso regression was used to develop a prediction model based on hub genes. Expression of the pyroptosis-related gene GSDMB was also investigated at the tissue and cellular levels. Results: Two molecular subtypes were identified based on the clustering of pyroptosis-related genes. Cluster 1 was associated with activation of classical oncogenic pathways, especially the angiogenesis pathway. Cluster 2 was associated with activation of immune-related pathways and high levels of immunosuppressive cells, exhausted CD8+ T cells, and tumor-associated fibroblast infiltration. Clusters 1 and 2 were thus defined as the angiogenic and inflamed subtypes, respectively. The two subtypes were predictive of the response of ccRCC to anti-angiogenic therapy and immunotherapy, with Cluster 1 patients benefiting from anti-angiogenic therapy and Cluster 2 patients showing better response to anti-PD1 inhibitor therapy. Furthermore, a 9-gene expression signature (HJURP, NUF2, KIF15, MELK, TPX2, PLK1, CDCA3, CTLA4, FOXP3) was identified that could predict outcome and response to immune checkpoint blockade therapy in test cohorts. Finally, GSDMB was found to be involved in the development of renal clear cell carcinoma. Conclusions: These results on pyroptosis-related genes in ccRCC provide a theoretical basis for understanding molecular heterogeneity and for the development of individualized treatment strategies.